2005
DOI: 10.1007/s10290-005-0040-x
|View full text |Cite
|
Sign up to set email alerts
|

The Rise of China: Prospects of Regional Trade Policy

Abstract: Economic integration, trade forecasting and simulation, gravity model, China,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 24 publications
(26 reference statements)
1
15
2
Order By: Relevance
“…From this result, they suggested that a reduction on exchange rate risk may occur if the global transactions of multinational firms increase. The finding about ASEAN participation is opposite with the result of Abraham and Hove (2005). These authors found that being ASEAN members, their bilateral trade would increase.…”
Section: Literature Reviewcontrasting
confidence: 54%
See 4 more Smart Citations
“…From this result, they suggested that a reduction on exchange rate risk may occur if the global transactions of multinational firms increase. The finding about ASEAN participation is opposite with the result of Abraham and Hove (2005). These authors found that being ASEAN members, their bilateral trade would increase.…”
Section: Literature Reviewcontrasting
confidence: 54%
“…Common language and population size contribute to the increase in trade. However, unlike Abbas and Waheed (2015), Abraham and Hove (2005) found insignificant impact of exchange rate variable. Surprisingly, joining ASEAN and APEC did not much contribute to the export flow for the region, whereas the export flow mainly depends on growth, trade barriers and common languages.…”
Section: Literature Reviewmentioning
confidence: 70%
See 3 more Smart Citations